Singlet oxygen production by a polypyridine ruthenium (II) complex with a perylene monoimide derivative: A strategy for photodynamic inactivation of Candida albicans - Maia, Paulo José Sousa; de Aguiar, Inara; dos Santos Velloso, Marisol [UNESP]; Zhang, Dong; dos Santos, Edjane Rocha; de Oliveira, Jonatas Rafael [UNESP]; Junqueira, Juliana Campos [UNESP]; Selke, Matthias; Carlos, Rose Maria (Elsevier, 2018)
We report the synthesis, optical, electrochemical and electronic properties of a new perylene derivative and its Ru(II) complex, namely N,-(5-amino-1,10-phenantroline)perylene-3,4,9,10-tetracarboximonoimide (pPDI) and Bis(1,10-phenanthroline)(N-(5-amin-1,10-phenantroline)perylene-3,4,9,10-tetracarboxi monoimide)ruthenium(II) hexafluorophosphate, [Ru(phen)2(pPDI)]2+ ([PF6]−)2. The molecular structures of the compounds were elucidated by FTIR, mass spectrometry, elemental analysis (CHN) and DFT calculations. Their optical and electrochemical properties were investigated by absorption and fluorescence spectroscopy and cyclic voltammetry. The spectroscopic and electrochemical studies for both the pPDI and the perylene monoimide metal complex show that Ru2+ coordination does not affect the optical and electrochemical properties of the free perylene bisimide ligand. The Ru complex exhibits emission lifetimes of 5.06 ns (48.1%) and 156 ns (51.9%), resulting from emission of the pPDI ligand and 3MLCT, respectively. The pPDI triplet excited state in the title chromophore is able to sensitize the production of singlet oxygen (1O2). Using a time-resolved laser system, we measured the quantum yield for the production of singlet oxygen (ΦΔ) to be 0.26 for cis-[Ru(phen)2(pPDI)]2+. Candida albicans is recognized as the most common fungal pathogens, causing superficial infections of the skin and mucous membranes. Resistance of C. albicans strains against classical antifungal agents such as fluconazole has increased considerably, which drives the search for new therapeutic alternatives. In the present study, we report that our new Ru-perylene complex can indeed be used to kill the bacterium C. albicans. The fungicidal activity of cis-[Ru(phen)2(pPDI)]2+ against C. albicans was evaluated in the presence of C. albicans cultures in the dark and in the presence of light. After exposure to 12.5 μM of cis-[Ru(phen)2(pPDI)]2 in the presence of light for 180 s, C. albicans showed a decrease of 50% in its concentration compared to the same experimental conditions in the dark.
Keywords: Candida albicans; Photodynamic therapy (PDT); Photoluminescence; Ruthenium polypyridine complex; Singlet oxygen